Original Jurisdiction of the Supreme Court of Pakistan Article 184 (3) of the Constitution of Pakistan, 1973 (Journal of Social Sciences Review, 2023)
The Supreme Court of Pakistan, under article 184 (3) of Pakistan, can act on its own or on the application of any person with the condition that if the SC considers that any of the rights mentioned in the Fundamental Rights Chapter, is violated and that rights involve the public importance. The invocation of the original jurisdiction of the Supreme Court, also known as Suo Motu under article 184 (3), is a buzzword known to all and sundry in the country. The excessive invocation of this article 184(3) generates a debate in the legal community about whether Apex Court is encroaching on the legislature and executive functions. The debate involves judicial activism and judicial restraint.  One common objective exists that by taking excessive Suo motu, there is no appeal against the order of SC; hence fundamental rights of access to justice are violated, and on the other hand, the doctrine of separation of power though not expressly embodied in our Constitution but exist; that every organ of the State should remain within its sphere and mutual respect be given to every other organ of the State. Another restriction in taking Suo motu is the express word of article 184 (3) says that without the prejudice of the provisions of article 199, the SC can act.
Keywords: Original jurisdiction; Enforcement of Fundamental Rights; Encroachment; Organ of the State; Separation of Powers; Right of Appeal; State; Access to Justice; Public Importance; Locus Standi; Violation